Step
*
1
of Lemma
geom-sum-int
1. a : ℤ
2. n : ℕ
3. ((1 + (-a)) * Σ(a^(0 + i) | i < n - 0)) = (1 + (-a^n)) ∈ ℤ
⊢ ((1 - a) * Σ(a^i | i < n)) = (1 - a^n) ∈ ℤ
BY
{ (NthHypSq (-1) THEN RepeatFor 2 ((EqCD THEN Auto))) }
Latex:
Latex:
1.  a  :  \mBbbZ{}
2.  n  :  \mBbbN{}
3.  ((1  +  (-a))  *  \mSigma{}(a\^{}(0  +  i)  |  i  <  n  -  0))  =  (1  +  (-a\^{}n))
\mvdash{}  ((1  -  a)  *  \mSigma{}(a\^{}i  |  i  <  n))  =  (1  -  a\^{}n)
By
Latex:
(NthHypSq  (-1)  THEN  RepeatFor  2  ((EqCD  THEN  Auto)))
Home
Index